2014
DOI: 10.1103/physrevb.90.045207
|View full text |Cite
|
Sign up to set email alerts
|

Self-consistent relativistic band structure of theCH3NH3PbI3perovskite

Abstract: The electronic structure and properties of the orthorhombic phase of the CH 3 NH 3 PbI 3 perovskite are computed with density functional theory. The structure, optimized using a van der Waals functional, reproduces closely the unit cell volume. The experimental band gap is reproduced accurately by combining spin-orbit effects and a hybrid functional in which the fraction of exact exchange is tuned self-consistently to the optical dielectric constant. Including spin-orbit coupling strongly reduces the anisotrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
156
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(182 citation statements)
references
References 46 publications
25
156
0
Order By: Relevance
“…Direct calculations of the Kane energy predict it to be in the range 5.3 -6.3 eV for these materials 25,37 although recent theoretical mass values suggest a higher value 24,34 . Fig 5 shows that the reduced mass is quite well described using the band gap obtained from Eq.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct calculations of the Kane energy predict it to be in the range 5.3 -6.3 eV for these materials 25,37 although recent theoretical mass values suggest a higher value 24,34 . Fig 5 shows that the reduced mass is quite well described using the band gap obtained from Eq.…”
Section: Resultsmentioning
confidence: 99%
“…This value compared with the thermal energy (kT 25 meV at 300K) determines whether the photo created carriers will dissociate or will need to be separated by an additional junction in a PV device. Until very recently the reported values of binding energy were highly controversial and covered a wide range: For MAPbI 3 values from 2 to 55 meV 5,[22][23][24][25][26][27] have been reported with values at the lower end of the range now becoming more common in the literature [25][26][27] ; and for MAPbBr 3 it has been suggested that R * could be as high as 70 meV 5 . Recently, we 28 have shown that by using magneto optical studies an exact determination of the binding energy of the exciton and effective mass of the carriers for MAPbI 3 is possible at low temperatures from the measurement of sequences of higher states for the excitonic transitions and the quantization of the free carrier states into Landau levels.…”
Section: Introductionmentioning
confidence: 99%
“…The DOS is approximately parabolic on a scale of several hundred meV around the band edges [12,20,32,33], in contrast to the typical square-root behavior of threedimensional semiconductors with parabolic bands. Accounting for this particular DOS, we use a modified leading-edge method to determine the position of the highest-energy VB.…”
mentioning
confidence: 83%
“…The parameters are the effective mass m * of the bands and the Rashba parameter α. The measured VB dispersion of CH 3 NH 3 PbBr 3 deviates from a parabola, but is closer to a hyperbola or even a cone, consistent with the parabolic DOS [12,20,32,33]. The resolution of our experiment is insufficient to reliably extract effective masses at the maximum of the bands.…”
mentioning
confidence: 85%
“…In fact, the comparison between the crystal radii measured by HRTEM and the reported estimated values of Bohr radius (R B ≈ 3 nm), [18][19][20][21][22] …”
Section: Doi: 101002/adom201601087mentioning
confidence: 99%